Effect of Partial Replacement of Coarse Aggregates in Concrete by Waste Tyre Rubber Aggregates with NAOH Solution in Rigid Pavements (International Journal of Innovative Research in Engineering & Management, 2022)
This study was intended to research the  partial replacement of coarse aggregate with shredded  rubber. The rubber used in the study was kept in three  conditions. The shredded rubber was either untreated,  treated with NAOH and treated with cement paste before  being used in concrete. M20 mix of concrete was used in  this study. The compressive strength, flexural strength and  split tensile strength of concrete after 28 days of curing for  replacement of rubber in the percentages of 5%,10% and  15% was done. The results show that there is a decrease in  workability as the percentage of rubber is increased for all  of the conditions of the shredded rubber treatment. The  compressive strength test result show that there is a  decrease in strength as the percentage of rubber is  increased. However, when treated rubber is introduced the  value of compressive strength improves. The flexural  strength test results show that the maximum value of  flexural strength is obtained at 5% replacement of rubber  for treatment with NAOH. The results indicate that treated  rubber specimens have more flexural strength when  compared with the values of untreated rubber specimens.  The split tensile strength shows that the value of split  tensile is maximum for 15% replacement of rubber and for  treatment with NAOH. The value of split tensile decreases  as the percentage of rubber is increased however an  improvement is seen as treated rubber is used to replace  coarse aggregate.
Keywords: Coarse Aggregate; Waste Tyre Rubber Aggregates; NAOH Solution; Rigid Pavements